STUDY OF SOLAR RADIATION AND SUN LOCATION AT MIDSUMMER OF A SPECIFIC GEOGRAPHIC POSITION (FUDMA JOURNAL OF SCIENCES, 2023)
Incoming solar radiation is the primary driving force for globes biological, physical and industrial systems. Cognition of the amount of solar radiation at various geographic emplacements is desirable for application in such varied disciplines as civil engineering, agriculture, meteorology, ecological research, environmental assessment, forestry and solar energy utilization. This paper introduces the most important parametric quantity such as solar zenith angles, solar Azimuth angle, Surface incidence angle and provides the location of the sun at any time and at any position using SPA (Solar Position Algorithm). Specific case has been studied to analyze the pattern of solar radiation and the solar path at June solstice with two neighboring day before and after the solstices. The results bespeak that the proposed framework can be successfully used to guesstimate the tract of the sun during all the seasons of year for studying position and for considering day, using as input the observer latitude (degrees), observer longitude (degrees), average local pressure, average local temperature and latitude (m). The result of this study shows that the maximum value of solar radiation is obtained at an azimuth angle of  throughout the solstice while Topocentric zenith angle and surface incidence angle has the same values
Keywords: Geographical emplacement, Solar zenith angles, Solar Azimuth angles, Solar Position Algorithm